2020
DOI: 10.1111/nep.13827
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease is a very significant comorbidity for high risk of death in patients with COVID‐19 in Mexico

Abstract: Chronic kidney disease (CKD) is a recognized public health problem and key determinant of poor health outcomes. In Mexico, this condition has been associated with high and significant risk of death in COVID‐19 patients; however, not enough attention has been given to the vulnerable population as the increasing numbers and fatality rates suggest. This study evaluated the effect of interaction between CKD condition and other risk factors (sex, diabetes, hypertension and obesity) on the survival rate of positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…We were not able assess the effect of recent use of systemic corticosteroids in asthmatic patients, which has been shown to be a significant risk factor for adverse outcomes in patients with COVID-19 rather than history of asthma alone [27, 31]. CKD alone did not increase mortality risk, which could be due to the low number of patients with only CKD included in our study since CKD has been found to be a risk factor in others [27, 32]. However, the role of CKD as an individual risk factor for adverse outcomes in COVID-19 should be explored since CKD is often present in combination with DM and hypertension [33], which were individual risk factors in our study.…”
Section: Discussionmentioning
confidence: 94%
“…We were not able assess the effect of recent use of systemic corticosteroids in asthmatic patients, which has been shown to be a significant risk factor for adverse outcomes in patients with COVID-19 rather than history of asthma alone [27, 31]. CKD alone did not increase mortality risk, which could be due to the low number of patients with only CKD included in our study since CKD has been found to be a risk factor in others [27, 32]. However, the role of CKD as an individual risk factor for adverse outcomes in COVID-19 should be explored since CKD is often present in combination with DM and hypertension [33], which were individual risk factors in our study.…”
Section: Discussionmentioning
confidence: 94%
“…The certainty of evidence was moderate for at least a large increase in mortality from COVID-19 for people aged 60-69 years versus <60 years (11 studies, n=517,217) [24, 48, 63, 68, 71, 84, 92, 93, 98, 101, 106, 113], people with two or more versus no comorbidities (4 studies, n=189,608) [48, 59, 101, 105], and for people with (versus without): Down syndrome (1 study, n>8 million) [35], type 1 and 2 diabetes (1 study, n>8 million) [35], end-stage kidney disease (1 study, n>8 million) [35]; epilepsy (1 study, n>8 million) [35]; motor neuron disease, multiple sclerosis, myasthenia gravis, or Huntington’s disease (as a grouping; 1 study, n>8 million) [35]. The magnitude of association with mortality is probably (moderate certainty) very large for Down syndrome, and may (low certainty) be very large for age 60-69 years, and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…We were not able assess the effect of recent use of systemic corticosteroids in asthmatic patients, which has been shown to be a significant risk factor for adverse outcomes in patients with COVID-19 rather than history of asthma alone [16,20]. CKD alone did not increase mortality risk, which could be due to the low number of patients included in our study since CKD has been found to be a risk factor in others [16,21]. However, the role of CKD as an individual risk factor for adverse outcomes in COVID-19 should be explored since CKD is often present in combination with DM and hypertension [22], which were individual risk factors in our study.…”
Section: Sars-mentioning
confidence: 88%